Current neoadjuvant treatment options for HER2 positive breast cancer - Abdel-Razeq H (Dove Medical Press, 2011)
Hikmat Abdel-Razeq, Lina MareiSection of Hematology and Medical Oncology, Department of Internal Medicine, King Hussein Cancer Center, Amman, JordanAbstract: Approximately one quarter of patients with breast cancer demonstrate amplification of the human epidermal receptor type 2 (HER2) gene, the expression of which is associated with a relatively poor prognosis independent of other clinical and pathologic variables. Trastuzumab, a humanized recombinant monoclonal antibody specifically directed against the HER2 receptor, has been shown to be biologically active and of considerable clinical utility in HER2-positive breast cancer patients. Neoadjuvant chemotherapy has been used in breast cancer to downstage the tumor and increase the opportunity for breast-conserving surgery. Preoperative chemotherapy can also serve as an in vivo testing of chemotherapy sensitivity. Additionally, a pathologic complete response is usually a surrogate marker of disease-free survival. Following the successful use of trastuzumab in the metastatic and adjuvant settings, many clinical trials have recently reported the successful use of anti-HER2 therapy in combination with different chemotherapy regimens in the neoadjuvant setting with a significantly higher pathologic complete response. With the recent introduction of new anti-HER2 drugs, interest has shifted toward dual HER2 blockade. Two such studies were recently reported, both showing a significant advantage of dual anti-HER2 therapy using lapatinib or pertuzumab in addition to trastuzumab and chemotherapy. However, several key questions need to be investigated further, such as the preferred combination chemotherapy and the optimal duration of trastuzumab in patients who achieve a pathologic complete response following preoperative chemotherapy with trastuzumab. These issues and others are discussed in this review.Keywords: neoadjuvant, breast cancer, trastuzumab, pertuzumab, lapatinib